Business Models for Negative Emissions From Waste-to-Energy Plants - Torvanger, Asbjørn (Frontiers in Climate, 2021)
Negative emissions of carbon dioxide will likely be needed to meet the less than 2 °C warming above the pre-industrial level goal of the Paris Agreement. A major technology option is combining Biomass Energy with Carbon Capture and Storage (BECCS) in the industry and power sectors. Biogenic waste contributes a major share for the numerous waste-to-energy plants around the world. This implies that adding a CCS facility to a waste-to-energy plant could establish a value chain for negative carbon dioxide emissions. Hence a waste-to-energy plant could deliver four services to society: waste management and avoided pollution, service district heating system, remove carbon dioxide from fossil-based waste categories, and generate negative carbon dioxide emissions from biogenic waste. A major barrier to deploying Bio-CCS at a waste-to-energy plant is a high investment and operation cost for the carbon dioxide capture plant, combined with lacking reward for the negative carbon dioxide emissions. In this paper I explore promising business models that could incentivize owners of waste-to-energy plants to install CCS facilities, assuming that government has established an infrastructure for transportation and permanent storage of carbon dioxide, as well as the basic framework for accounting for negative emissions. The business models are either founded on waste renovation customers being able and willing to pay for the additional cost of producing negative emissions of carbon dioxide directly or through certificates, or investments in CCS being incentivized by government through a guaranteed price or tax rebates for negative emissions of carbon dioxide.